Surgery of Complex Abdominal Wall Defects : Practical Approaches - Latifi, Rifat (Springer International Publishing : Imprint: Springer, 2017)
As with the first edition, the second edition of this book covers the surgical anatomy of the abdominal wall, pathology of abdominal wall defects, such as hernias, enterocutaneous or entero-atmospheric fistulae, and indications for and surgical techniques used to reconstruct the abdominal wall from the practical stand point. In addition, through a number of illustrations, the placement of mesh in the abdominal wall reconstruction as well as manipulations of patient's tissue including lateral compartment release techniques and other tissue transfer techniques are described in detail. The text also covers reconstruction of complex contaminated abdominal wall defects in patients with complex enteric fistulae, stomas, defects created after the excision of previously placed infected prosthetic mesh, and defects associated with acute tissue loss after severe trauma or necrosis of abdominal wall such as necrotizing soft tissue infections. Complex abdominal wall defects in the pediatric population and long-term outcomes and durability of these repairs are also addressed. The second edition of Surgery of Complex Abdominal Wall Defects is written by experts in their respective areas from around the world and has been updated thoroughly. As with the first edition, it will continue to serve as a guide for current practice for surgeons, including general, trauma, acute care, plastic and reconstructive surgeons.